What dimensions of women’s empowerment in agriculture matter for nutrition-related practices and outcomes in Ghana? - Malapit, Hazel J.; Quisumbing, Agnes R. (International Food Policy Research Institute, 2014)
This paper investigates linkages between women’s empowerment in agriculture and the nutritional status of women and children using 2012 baseline data from the Feed the Future population-based survey in Ghana. The sample consists of 3,344 children and 3,640 women and is statistically representative of the northernmost regions of Ghana where the Feed the Future programs are operating.